The evaluation of the research on the social sciences in Turkey: A scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the research on the Social Sciences carried out by the researchers in Turkey and published during the last three decades based on the Social Sciences Citation Index (SSCI) together with the underlying incentive structures and its implications using the scientometric techniques. The results of this study reveal that the research output on the Social Sciences and the citations received have grown exponentially during this period especially during the 2000s with paralleling enormous changes in the research landscape. However, the research performance of the researches in Turkey in the fields of Social Sciences (11,835 papers and 54,447 citations) has lagged significantly behind the comparative performance of Turkey in the Sciences indexed by the Science Citation Index-Expended (SCI-E). The US, England, and Canada have been the three most prolific collaborating countries. The "Middle East Tech Univ" has been the most prolific institution and "Tan U" of "Cukurova Univ" has been the most prolific author. "Kuram ve Uygulamada Egitim Bilimleri" (Theoretical and Applied Educational Sciences) has been the most prolific journal, whilst "Education & Educational Research" has been the most prolific subject area. "H-index" was 65 and "Rosser et al." [1] had the highest impact on the literature. The scientometric analysis has a great potential to given valuable insights into the evolution of the research on the Social Sciences in Turkey, complementing the scientometric studies in the other fields such as renewable energies as well as higher education providing a unique insight on the incentive structures for all the key stakeholders in the field. It was concluded in this context that the incentive structures have not been well designed to produce superior research performance in Social sciences in Turkey as in Sciences indexed by the SCi-E such as Engineering and Health Sciences especially in the design of the rules for the academic appointments and promotions in universities as the number of papers and number of citations received per member of staff in 2010 for 11,518 researchers were 0.17 and 0.07, respectively.
Keywords: Social Sciences; SSC; Iincentive structures; Research evaluation; Research productivit; Scientometrics; Web of Knowledge